2007
DOI: 10.1111/j.1471-4159.2007.04991.x
|View full text |Cite
|
Sign up to set email alerts
|

SPAR2, a novel SPAR‐related protein with GAP activity for Rap1 and Rap2

Abstract: Spine‐associated RapGAP 2 (SPAR2) is a novel GTPase activating protein (GAP) for the small GTPase Rap that shows significant sequence homology to SPAR, a synaptic RapGAP that was reported to regulate spine morphology in hippocampal neurons. SPAR2, like SPAR, interacts with the recently described synaptic scaffolding protein ProSAP‐interacting protein (ProSAPiP), which in turn binds to the PDZ domain of ProSAP/Shank post‐synaptic density proteins. In subcellular fractionation experiments, SPAR2 is enriched in s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
53
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(54 citation statements)
references
References 51 publications
1
53
0
Order By: Relevance
“…Fez1 domains are approximately 200 aa long and were found to specifically interact with the C termini of actin binding SPAR molecules (30) that localize at PSDs. It seems that this interaction is secured by redundant short interaction motifs because we found that even partial SPAR C-terminal sequences are efficiently bound to the LAPSER1 Fez1 domain.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Fez1 domains are approximately 200 aa long and were found to specifically interact with the C termini of actin binding SPAR molecules (30) that localize at PSDs. It seems that this interaction is secured by redundant short interaction motifs because we found that even partial SPAR C-terminal sequences are efficiently bound to the LAPSER1 Fez1 domain.…”
Section: Discussionmentioning
confidence: 99%
“…E, to determine the interaction partner of the Fez1 domain, we performed a yeast two-hybrid screen employing the Fez1 domain as bait. To our surprise all 11 positive clones were coding for members of the SPAR family of proteins (30). The shortest prey clone was only ϳ200 aa long, indicating that the very C-terminal part contains the interaction motif.…”
Section: Lapser1 Binds To and Coclusters With ␤-Catenin And Colocalizmentioning
confidence: 96%
See 1 more Smart Citation
“…37,38 Neurons were transfected at DIV7 and fixed with 4% paraformaldehyde (PFA) at DIV21. Stainings with synaptic and dendritic markers were performed as described above.…”
Section: Subcellular Fractionation Immunoblotting and Immunocytochemmentioning
confidence: 99%
“…All Sipa family members share common domains, namely an N-terminal RapGAP domain (Rap-GTPase activating domain), a PDZ domain and a Cterminal coiled-coil domain that was found to harbor a leucine zipper (Wendholt et al, 2006). So far, Sipa1l1-3 have been analyzed mainly with respect to their synaptic function in the central nervous system (Dolnik et al, 2016;Pak et al, 2001;Spilker et al, 2008).…”
Section: Introductionmentioning
confidence: 99%